A scoping review of cross-cultural experiences of siblings of individuals with intellectual and developmental disabilities in the United States. (May 2021) - Lee, Chung Eun; Hagiwara, Mayumi; Black, Hannah
Abstract: Background: Siblings undergo unique experiences in growing up with brothers and sisters with intellectual and developmental disabilities (IDD). Although sibling relationships or adjustments among individuals with IDD have received greater attention from the disability field, there has been still less attention to how cultural identities (e.g., race, ethnicity) may influence experiences of siblings of individuals with IDD. Aim: This study used scoping review methodology to understand cross-cultural experiences of siblings of individuals with IDD in the United States. Method: Eight articles met inclusion criteria, using the PubMed, Web of Knowledge, PsycINFO, and ERIC databases. Results: Studies reported the impact of cultural identities on sibling emotional and behavioral functioning, school functioning, and caregiving responsibilities. Conclusions: The need for culturally responsive sibling interventions and implications for international contexts is discussed.